The experience of non-clinical research staff during the COVID-19 pandemic: key learning points. Issue 7 (2nd July 2022) - Gosling, Amy; Manley, Alice; Radovanovic, Charlotte; Willams, Rowena
Abstract : The COVID-19 pandemic has created and exacerbated many challenges and difficulties, but research departments across the UK were able to adapt and delivery research at an unparalleled rate. This article discusses the work of a large research department and the role that non-clinical staff played in coordinating a considerable research response to the pandemic. The outputs of the team during this time will be discussed, as well as discussion of how individuals adapted and how change management can be used to identify key recommendations and learning points. These learning points should be considered in any future crisis situations when managing non-clinical healthcare teams, both in research and the wider NHS.